Theoretical and Experimental Study of Water Storage Tank with Earth Water Heat Exchanger in Hot Climates Regions - Dakhil, Amer Abduladheem; Hammadi, Salman Hashim (Basrah Journal for Engineering Sciences, 2022)
Concerning commercial and residential buildings, one of the major parts related to water supply systems is the water storage tanks. For gravity- fed buildings, the tanks must be installed on the roof. In Iraqi summer, the temperature of water in storage tanks reaches above 50 °C due to high solar intensity, which makes it inappropriate for domestic usage. One of the proposed solutions to overcome this problem is feeding the hot water into an earth-water heat exchanger (EWHE) which consists of a set of buried pipes installed underground level to reduce its temperature. The storage tank and the earth-water heat exchanger were studied experimentally and theoretically by using ANSYS 20/FLUENT software to estimating the water temperature in the storage tank and the temperature of the water leaving the EWHE. The most important results obtained theoretically and experimentally that when using pipe length, pipe diameter, and mass flow rate of 100 m, 0.016 m, 0.7 LPM respectively, at a depth of 3 m, the water temperature decreases by about 15 °C. Also, the results have shown a good agreement between the experimental and theoretical works. One can conclude that an earth-water heat exchanger is an effective way to decrease the temperature of the storage water to an acceptable level for domestic usages.